Forage Business at Breed Source Area of Ruminansia in Central Java Province - Muatip, Krismiwati; Widiyastuti, Titin; Hidayat, Nunung Noor; Purwaningsih, Hermin; Purwanto, Eko; Setya, Ghanis Ginanjar (ANIMAL PRODUCTION, 2017)
Kebumen district is one of beef development centers in Central Java that requires numerous forage supplies (HPT). Farmers without personal foraging area have to buy forages almost on a daily basis. Forage business is an emerging and prospective business sector to improve farmersâ€™ welfare particularly the income. Government is therefore expected to support in terms of facility and infrastructure to maintain a sustainable business practice. Â The aim of this study was to investigate the necessity of forage business in cattle development center in Kebumen district, forage marketing channel, forage business revenue, profit margin, R/C ratio and government support in terms of infrastructure or policy related to forage business.